Teacher Readiness in the Face of the Fifth Industrial Revolution: A Human-Centred Technological Paradigm in Education - Azim, Rabbimova (PT. BATARI EDU CALYA, 2025)
The advent of the Fifth Industrial Revolution (5IR) has ushered in a paradigm shift in education, emphasising the synergy between human intelligence and technological innovation. This study aims to analyze teacher readiness in adapting to the transformative demands of 5IR by employing a systematic literature review (SLR) method with a qualitative descriptive approach. The review synthesises findings from scholarly publications between 2019 and 2024, encompassing aspects such as digital literacy, pedagogical innovation, ethical awareness, and adaptive competence. Results reveal that teacher readiness in the 5IR era comprises four core dimensions: technological proficiency, pedagogical adaptability, psychological resilience, and ethical responsibility. Despite remarkable progress in digital pedagogy, substantial challenges persist, including disparities in digital literacy, inadequate infrastructure, and limited professional development opportunities. The findings also highlight that continuous professional training, collaboration among educators, and strategic partnerships between schools and the technology industry significantly enhance teacher preparedness. Teachers are urged to transform into “edupreneurs,” combining innovation, empathy, and ethical awareness to design inclusive and human-centered learning environments. Ultimately, teacher readiness for 5IR requires not only the mastery of digital tools but also the cultivation of humanistic and reflective pedagogical practices that sustain meaningful learning in a rapidly evolving world. This study contributes to the growing discourse on education transformation by offering a conceptual framework to guide teacher development programs in fostering resilient, innovative, and ethically grounded educators who can thrive in the technological and humanitarian dimensions of 5IR education.